Writing the self, creating community : German women authors and the literary sphere, 1750-1850 - Krimmer, Elisabeth, 1967-; Nossett, Lauren, 1986- (Women and gender in German studies., 2020)
"This volume examines the world of German women writers who emerged in the burgeoning literary marketplace of eighteenth-century Europe"--